Aplicação de um modelo de dimensionamento para câmara de expansão de sistemas de distribuição na indústria de petróleo e gás - Rocha, Jaqueline de Azevedo (2022)
The separation of the product phases obtained in oil extraction wells is a fundamental part of oil and gas production. However the separators used have large dimensions and high cost of installation, operation and maintenance. In this paper several types of cyclonic separators will be discussed, detailing their main characteristics, especially the VASPS separator – Vertical Annular Separation and Pumping System. This work aims to promote and present a study on the applications of algebraic modeling of the liquid film flow in the expansion chamber of a VASPS separator for vertical flows, using a mathematical model from the reference literature, applying and adapting a theoretical model in a real distribution system in the oil and gas industry. The study will be promoted through simulations of the algebraic model in a Python program. The simulations were performed for vertical downward and upward flows, using both water and oil as the liquid, using real data from vertical oil and gas flows. The simulations were performed by varying the separator chamber diameter from 10 to 50 inches, and the nozzle diameter from 1 to 8 inches. The properties of the oil used as the working fluid were also varied. The analyses were then performed using the resulting graphs generated by the program.The simulations for vertical downward flow obtained excellent results, both for water and oil. The simulations for vertical upward flow, however, did not obtain satisfactory results, só it was possible to conclude that it is necessary to make some adjustments in the algebraic model presented in the literature, só that it can correctly describe the vertical upward flow in the expansion chamber of the VASPS separator.